Effect of Sago Pulp (Arenga pinnata) Supplementation in Rations on Beef Cattle Performance - Pradisya Halimatu Sa’diah; Mochammad Yasrul Fathurahman; Aqila Anasya Putri; Hera Febriana Kurniawati; Nita Primastuti; Oktar Ramadhoni; Aan Andri Yano (JURNAL TRITON, 2025)
Sago pulp (Arenga pinnata) is an abundant agricultural waste in Indonesia and has potential as an alternative feed ingredient for beef cattle due to its high crude fiber content, making it an economical and sustainable option. This study aimed to explore the effect of sago pulp supplementation in rations on the performance of Simmental, Limousin, and Brangus cattle. The study was conducted from May 10, 2023 to June 1, 2023 at a commercial cattle farm in Gunung Kidul Regency, Yogyakarta Special Region, Indonesia. A total of 15 beef cattles, consisting of 5 cattles each of Limousin, Brangus, and Simmental breeds, were used in this study. This exploratory study was conducted with a uniform inclusion level of 29.2% sago pulp for all cattle. Data were analyzed using ANOVA test, with Honesty Significant Difference (HSD) for further test to separate the means if significant effects were found. The results showed that sago pulp supplementation had no significant effect on Average Daily Gain (ADG), Feed Conversion Ratio (FCR), and Feed Cost per Gain (FCG) (P > 0.05). On the other hand, a significant effect was observed on the increase of final body weight in all three cattle breeds, especially Simmental (P < 0.05). In conclusion, genetic factors play an important role in the response of cattle to sago pulp supplementation. This study is expected to provide a scientific basis for the use of sago pulp as an alternative feed for beef cattle of various breeds